DIFFERENCES BETWEEN HEALTH EDUCATION WITH VIDEO AND COMIC DIGITAL THROUGH WHATSAPP TO KNOWLEDGE HIV/AIDS IN JUNIOR HIGH SCHOOL 1 SUMBERPUCUNG - Della Salsa D'azzuri; Tri Nurhudi Sasono; Nia Agustiningsih (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2020)
Health education about HIV / AIDS is very important given to adolescence to reducetransmission of HIV /AIDS. This study aimed to determine the differences in healtheducation using video and digital comics through Whatsapp on the knowledge of HIV/ AIDS in adolescents at Junior High School 1 Sumberpucung. This study used a QuasiExperimental with 36 respondents divided into 18 respondents for the video group and18 respondents for the digital comic group. The sample collection technique was obtainedusing Simple Random Sampling. Data was collected a questioner sheet. Statistical testsuse paired T-tests to measure differences in knowledge before and after education isgiven to each group and unpaired T-tests are used to determine the effectiveness of videoand digital comic media. The results of the study using the paired T-Test showed thatthere were differences in knowledge of HIV / AIDS in adolescents after being given healtheducation using video and digital comic through WA with the result of an increase in theaverage digital video group 1.61 while the digital comic group 0, 5 From the results ofthe unpaired T-Test, P-value of 0.022 was obtained. The result showed that video moreeffective to improve the knowledge of the adolescence than digital comics so that videocan be used to the media in the provision of education health or can also be the media oflearning in school.